2023
DOI: 10.25259/anmrp_20_2022
|View full text |Cite
|
Sign up to set email alerts
|

Any correlation between severity of symptoms and the adenoid nasopharyngeal ratio?

Abstract: Objective: Adenoid Hypertrophy is a common childhood condition that presents with mouth breathing, nasal discharge, snoring and sleep apnea. Lateral Nasopharyngeal X-ray aids diagnosis and assessment of patency of the Nasopharyngeal air column through Adenoid Nasopharyngeal Ratio (ANR). This study aims to correlate ANR with symptoms and signs of Adenoid Hypertrophy. Material and Methods: A retrospective study conducted in the Ear, Nose and Throat/Head and Neck Surgery (ENT/HNS) Department of University of Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…[2] [4] Adenoid enlargement is uncommon or underestimated in adults [5] while common in children. [2] [4] [6] [7] It is reported that adenoid enlargement commences in early childhood up to the age of 6 years, then slowly atrophies at 8-10 years and completely disappears by the age of 16. [4] [7] [8] The primary symptoms of sinonasal polyposis are nasal obstruction and nasal discharge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] [4] Adenoid enlargement is uncommon or underestimated in adults [5] while common in children. [2] [4] [6] [7] It is reported that adenoid enlargement commences in early childhood up to the age of 6 years, then slowly atrophies at 8-10 years and completely disappears by the age of 16. [4] [7] [8] The primary symptoms of sinonasal polyposis are nasal obstruction and nasal discharge.…”
Section: Introductionmentioning
confidence: 99%
“…[9] [10] [11] Although, magnetic resonance imaging (MRI) may occasionally be required for further evaluation. [6] [12] The main objective of this article is to evaluate a rare occurrence of ethmoidal polyposis, adenoid enlargement and tympanic membrane perforation in an adult.…”
Section: Introductionmentioning
confidence: 99%